(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2015)
This paper aims to provide a philosophical reconstruction of Frankl’s Logotherapy. It clarifies his central concepts like ’person’, ’freedom’, ’responsibility’, ’value’ and ’meaning’. It will be argued that Frankl’s anthropology is not fully coherent and is based on strong metaphysical premises, which appears questionable from an existential point of view.